R&D impact in the changes of economic structure of population - Aliu Mulaj, Luljeta; Dedaj, But (Business: Theory and Practice, 2025)
Research and Development (R&D) plays crucial role in the technological progress, and thus it can be seen as facilitator of the economic development. It is widely known that the importance of the research is not only in economic aspect but also in the technologic aspect. On the other hand, not all of countries have possibility to develop such researches, as it requires huge financial support, and professional human capital. As a result of these investments and technological developments, changes on the employment rate in each sector are evident. The study is focused on measuring the impact of R&D in the changes of the economic structure of population. In the study are included thirty world countries divided in three groups: ten countries with largest GDP, ten with largest GDP per capita and ten Balkan countries. Structural Equation Model is used to measure the impact of almost three decades until pandemic COVID-19. From the analysis conducted, the results show that, investments in research and development and innovation have positive impact on the economic structural of population.